7P Multispectral immunofluorescence and computational imaging analysis define the prognostic role of T-cell infiltrates in gastric cancer. (15th December 2019) - Challoner, B R; von Loga, K; Woolston, A; Griffiths, B; Hewitt, L; Saito, Y; Sivamanoharan, N; Mansfield, D; Melcher, A A; Grabsch, H; Gerlinger, M
Abstract: Background: Gastric cancer (GC) is the 3 rd commonest cause of cancer mortality. T cells infiltrates are prognostic in other cancer types (Pagès 2018) but most studies in GC have used manual counting, lacked a validation cohort and were performed in Asian patients with often better outcomes than Western patients. The prognostic role of T cells hence remains poorly established in Western GCs. Methods: Tissue microarrays from 474 therapy naïve GCs resected in Leeds, UK, were split into discovery and validation cohorts and stained using multispectral immunofluorescence for CD8 (cytotoxic-), CD45RO (memory-), FOXP3 (regulatory-T cells), cytokeratin and DAPI. T cell densities were measured by computational image analysis. GCs were assigned to 5 equal sized density classes (C1 low to C5 high) for each marker and cancer specific survival (CSS) was assessed. Results: CD45RO (p = 0.000) and FOXP3 (p = 0.001) densities were significantly associated with CSS in the discovery cohort (n = 327). For both markers, C1 (low) and C5 (high) were associated with the shortest and longest CSS, respectively, C2 to C4 all showed similar CSS and were consolidated into an intermediate group. Reanalysis using low, intermediate and high groups showed significant associations of CD45RO (p = 0.024) and FOXP3 (p = 0.003) densities with CSS in the validation cohort (n = 147). TNM stage, CD45RO and FOXP3 densities were independent predictors of CSS in multivariate analysis of both cohorts. EBV positive (EBV+) and MMR deficient (dMMR) GCs are considered highly immunogenic GC subtypes. 20/475 GCs were EBV+ and 70% of these showed high CD45RO or FOXP3 densities. 51/488 were dMMR but only 38% were CD45RO or FOXP3 high, perhaps indicating the frequent acquisition of immune evasion mechanisms by dMMR GCs (von Loga 2019). Conclusion: This study identified and validated CD45RO and FOXP3 T cell infiltrates as independent prognostic markers in Western GC patients. This may enable personalized follow up or (neo)adjuvant treatment strategies. Whether high infiltrates are predictive of immunotherapy benefit should be assessed. Unexpectedly, high FOXP3 densities were associated with longer CSS, warranting studies into the role regulatory T cells in GC. Legal entity responsible for the study: Marco Gerlinger. Funding: National Institute for Health Research and Biomedical Research Council - Royal Marsden Hospital, Cancer Research UK, Schottlander Foundation. Disclosure: All authors have declared no conflicts of interest.